The application of Inca khipuas an accountability and managerial control tool - Schmidt, Paulo; dos Santos, José Luiz (Review of Business Management, 2017)
Purpose – This study aims to present the mechanisms of control and accountability used in the Inca society. Design/methodology/approach – For this purpose, a bibliographical and documental analysis regarding the use of khipus in this civilization was carried out, applying a qualitative approach. Findings – The results of the study indicate that the Inca khipu was the main instrument of tax registration and management adopted by the Inca empire. The Khipucamayocs were responsible for the production of the Khipu, asserting that the information generated and consolidated in the imperial khipu was correct, considering that these professionals paid with their lives in case of errors. Originality/value – The main contributions to accounting are related to the understanding of the origin of the development of tax control and accountability tools created in the Inca Empire, before the Spanish invasions, that contributed significantly to the development of the first American societies